RELASI MAKNA DALAM BAHASA MELAYU DIALEK MELAWI - Jamelia, Icha Nurma; Patriantoro, Patriantoro; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractIndonesian country has one language that become unifying nation languageÂ  that is Indonesian language, it is happen because Indonesia has various kind of language.This research is about local language. The method that use in this research is comparison method with qualitative as a form of the research. Technique of data collecting is induction techniques and skill method. Technique of data analysis is classification data, comparison, data analysis and conclusion of analysis result. Based on the result of analysis meaning relation in Malay Language Dialect of Melawi (BMDM )can be deducted that antonym BMDM by its nature is devided into four namely, absolute,Â  gradation, relation and hierarchy. There are 57 words in absolute antonym, there are 38 words in gradation, there are 38 words in relation and 7 words in heararchy. There ade 70 synonym in BMDM. There are 75 homonyms and 5 homographs in BMDM. There are 20 polysemics in BMDM. There is a lexical meaning in BMDM antonym meaning. The whole anonymous words contains a lexical meaning. There are cognitive meaning, connotative and emotive meaning in BMDM synonym meaning. There are referential and nonreferential meaning in BMDM homonym meaning. There are referential, nonreferential and idiomatic meaning ini BDMD polisemic meaning.Keyword: meaning of relation, dialect, Melawi.